The middlebrow Spanish Civil War film: a site of mediation between culture and history. - Laura J. Lee Kemp (Belphégor)
Films set during or immediately after the Spanish Civil War have a long tradition in Spain, one which spans the entire spectrum of filmic genres, from propaganda to musicals to art-house. This genre has not abated since the turn of the century, it has become increasingly ubiquitous and since the late 1990s, undeniably ‘middlebrow’. Yet this prolific genre, on the whole, is largely snubbed by films critics and academic researchers alike. The old adage of ‘oh not another civil war film’ remains widely recurrent in the press, but the fact that many, if not all, of these productions deal with narrative tropes that are of profound social relevance warrants further investigation. By analysing the primacy of emotion and affect in two films, Blind Sunflowers (Los Girasoles Ciegos, 2009) and The Sleeping Voice (La voz dormida, 2011), this article argues that civil war films constitute a sub-genre of the Spanish middlebrow which is exceptionally, yet controversially, well-suited to the exploration of socially and culturally traumatic themes.